Labour turnover and workers' well-being in the Ethiopian manufacturing industry - Sandra Kristine Halvorsen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
Manufacturing industry expansion is a central part of Ethiopia's growth and transformation agenda due to its potential for accelerated economic development and large-scale job creation, in particular for women. However, the industry is experiencing extremely high labour turnover rates, which is hampering the prospects of a successful industrialization of the country. Understanding the reasons for the high turnover may give important insights into the industry workings and how factory employment affects women's economic empowerment and well-being. Using a combination of survey data and qualitative interviews, the study highlights three main reasons for the high turnover: unrealistic expectations about wages and work efforts, poor working conditions, and difficulties combining domestic responsibilities with factory employment. In order to achieve social and economic development through industrial development, the Ethiopian government and firm managers need to take action to handle the turnover problem, making factory jobs safe, profitable, and a place for competence development.
Keywords: J22; J63; J81; 330; female labour supply; labour turnover; manufacturing industry development